2003
DOI: 10.1589/jpts.15.93
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Balance: Comparison of the Timed "Up and Go" Test and Functional Reach Test with the Berg Balance Scale

Abstract: Abstract.Objective: To compare the Timed "Up and Go" and Functional Reach tests to the Berg Balance Scale for concurrent validity in a broad adult population. Design: A prospective study of individuals with balance deficits. Setting: Neurological rehabilitation, skilled nursing, and acute care facilities. Subjects: Twenty subjects: 12 females and eight males, aged 38 to 86 years (µ=68, SD=14.5). Intervention: The order in which the three tests were performed on each subject was randomized and the scores from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 8 publications
6
67
0
1
Order By: Relevance
“…In this study correlation between these two tests was also found. However, Bennie et al 25 did not find significant correlation between these two tests.…”
Section: Resultsmentioning
confidence: 89%
“…In this study correlation between these two tests was also found. However, Bennie et al 25 did not find significant correlation between these two tests.…”
Section: Resultsmentioning
confidence: 89%
“…The original FRT involving one-arm reach, developed by Duncan et al 1) , is a popular method for assessing dynamic balance, but recently, twoarm reach has been put to wide use with the aim of eliminating the effect of trunk rotation and shoulder protraction [7][8][9][10][11][12][13][14] . However, to our knowledge, there are no reports which show a relationship between one-arm reach distance and trunk rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FR is inversely associated with recurrent falls, physical frailty, and physical changes [2][3][4] , as is COPE 5,6) . Although the original method uses reaching forward with one arm, recently, reach distance using two arms has been used to examine dynamic balance [7][8][9][10][11][12][13][14] . This is because it is considered by some researchers that two-arm reach excludes the influence of trunk rotatory flexibility on reach distance, thereby indicating dynamic balance more effectively and accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Values can be compared to normal age related times [62]. It is a test of functional mobility in older adults and has good correlation with gait speed (r = 0.745) [63] and the Berg Balance test (r = 0.47) [64]. Inability to complete the TUG has been reported to predict hospital length of stay in one recent study [65].…”
Section: Physical Functionmentioning
confidence: 99%